Aesthesis and perceptronium on the entanglement of sensation, cognition, and matter - Wilson, Alexander (University of Minnesota Press, 2019)
A new speculative ontology of aesthetics. In Aesthesis and Perceptronium, Alexander Wilson presents a theory of materialist and posthumanist aesthetics founded on an original speculative ontology that addresses the interconnections of experience, cognition, organism, and matter. Entering the active fields of contemporary thought known as the new materialisms and realisms, Wilson argues for a rigorous redefining of the criteria that allow us to discriminate between those materials and objects where aesthesis (perception, cognition) takes place and those where it doesn't. Aesthesis and Perceptronium negotiates between indiscriminately pluralist views that attribute mentation to all things and eliminative views that deny the existence of mentation even in humans. By recasting aesthetic questions within the framework of "epistemaesthetics," which considers cognition and aesthetics as belonging to a single category that can neither be fully disentangled nor fully reduced to either of its terms, Wilson forges a theory of nonhuman experience that avoids this untenable dilemma. Through a novel consideration of the evolutionary origins of cognition and its extension in technological developments, the investigation culminates in a rigorous reevaluation of the status of matter, information, computation, causality, and time in terms of their logical and causal engagement with the activities of human and nonhuman agents
Includes bibliographical references and index
Keywords: Materialismus; Ästhetik; Ontologie; Aesthetics; Materialism